Pengaruh Efektivitas Pelaksanaan Pengendalian Internal, Asimetri Informasi dan Ketaatan Aturan Akuntansi Terhadap Akuntabilitas Organisasi dengan Kecenderungan Kecurangan Akuntansi Sebagai Variabel Intervening (Studi Empiris pada SKPD di Kabupaten Muara Jambi) - Ahmad Soleh; Agus Maulana Hidayat; Asrini Asrini (J-MAS (Jurnal Manajemen dan Sains), 2019)
Based on the current conditions that the accountability of performance or financial responsibility for outcame on the use of budget in order to realize result oriented governance has not yet materialized, this shows the weakness of the Government's Internal Control System (SPIP) and Compliance with Accounting rules. The purpose of this study was to analyze the performance of the apparatus and public services in the Muaro Jambi district government so that the most appropriate strategies could be found in carrying out bureaucratic reforms in the government of Muaro Jambi Regency. This research was conducted in all SKPD in Muaro Jambi Regency. The data used in this study are secondary data collected from all agencies in the Jambi City Government, and the necessary literature and journal journals. The analytical model used is path analysis which consists of direct and indirect influences. The results showed that (1) The Effectiveness of Internal Control has a significant influence on Organizational Accountability, (2) Information Asymmetry has no significant effect on the Accountability of Regional Devices Organizations in Muaro Jambi Regency, (3) Compliance with Accounting Rules has no significant effect on the Accountability of District Regional Devices Muaro Jambi.